Case report: drug-induced melanosis in 21-year-old woman treated by gingival depigmentation - Indah Puti Rahmayani Sabirin; Zalfa Puspa Fakhira (Jurnal Medali, 2023)
Background: Oral pigmentation can be caused by long-term consumption, smoking or physiology. Drug induced melanosis is one of the oral pigmentation caused by long-term medication use. Changes in the color of the oral mucosa can be and provide local or systemic diagnostics, it is necessary to carry out a significant examination and findings from the patient properly.Case Report: The method used is a case report with primary data analysis obtained through anamnesis, as well as intra-oral examinationConclusion: The diagnosis of patients with drug induced melanosis with clinical features found in the gingiva of the maxillary and mandibular anterior teeth, this is because the patient has a history of bronchitis and has been taking antibiotics for a long time. To overcome this pigmentation, the patient underwent OHI and gingival depigmentation treatment and the results showed reduced gingival pigmentation after 1 month postoperatively.